Chinese theatre - Fu, Jin (Cambridge ; New York, NY : Cambridge University Press, 2012)
In this illustrated introduction Fu Jin explores the origins and development of Chinese theater from ancient opera to modern drama.
Uniform title Zhongguo xi ju. "Originally published by China Intercontinental Press as The art of Chinese theatre (9787508516837) in 2010"--T.p. verso. "Translated from the original Chinese by Wang Wenliang, Wang Huan, and Zhang Lina"--Cover flap.
MA
Keywords: Theater -- China -- History; Chinese drama -- History and criticism